Characteristics and trends of severe/critical COVID-19 cases in the Republic of Korea (January 2020 to August 2023) - Se-Jin Jeong; Shin Young Park; Boyeong Ryu; Misuk An; Jin-Hwan Jeon; So Young Choi; Seong-Sun Kim (Osong Public Health and Research Perspectives)
Objectives We analyzed the demographic and clinical characteristics of patients diagnosed with coronavirus disease 2019 (COVID-19), focusing specifically on severe/critical cases, and assessed the trends and rates of severity and fatality among these patients in the Republic of Korea. Methods Clinical data on patients with COVID-19 from January 20, 2020 to August 30, 2023 were collected from the Korea Disease Control and Prevention Agency’s database. We identified patients who progressed to severe/critical conditions and analyzed their demographic and clinical profiles. Severity and fatality rates were calculated and compared annually to track the disease progression over time. Results During the surveillance period, 34,572,554 COVID-19 cases were confirmed, among whom 38,112 (0.11%) progressed to severe/critical conditions. Most severe/critical cases occurred in individuals aged ≥60 years, with a notable increase in patients aged ≥80 years from 2022. The overall severity rate was 0.19%, with a fatality rate of 0.10%. However, the severity of cases gradually diminished during the study period. In 2022, the severity and fatality rates decreased to 0.14% and 0.09%, respectively. In 2023, while the severity rate remained stable at 0.15%, the fatality rate further decreased to 0.06%. Notably, throughout the study period, individuals aged ≥80 years had a significantly higher severity rate (2.44%), with a fatality rate of 1.75%. Conclusion These findings underscore the importance of prioritizing protection and management strategies for older adults and high-risk groups to mitigate the impact of COVID-19. Continued surveillance and analysis are essential to effectively control COVID-19 and minimize its burden on public health.